Fundamental statistical ideas in Math textbooks for elementary education in Nicaragua and Venezuela - Salcedo, Audy; Uzcátegui Pacheco, Ramón Alexander; Díaz-Levicoy, Danilo (IE Revista de Investigación Educativa de la REDIECH, 2021)
It is discussed how fundamental statistical ideas are incorporated into two collections of elementary Math textbooks through student activities. A content analysis was carried out to examine the statistics and probability activities in textbooks from Nicaragua and Venezuela, classifying them by grade and level of cognitive demand. The results indicate that the Nicaraguan collection addresses three of the seven ideas considered, although only one of them is found and is being worked on regularly. Venezuelan books also work on three ideas through activities for the student and two of them are present in one school level. Although both collections propose activities of high cognitive demand, the greatest emphasis is placed on routine and algorithmic tasks. A revision of both collections seems necessary if the statistical literacy of the citizen is to be supported. Teachers should propose complementary activities that cover ideas missing in books and activities with greater cognitive demand.